Molecular characterization and sequence phylogenetic studies on Theileria annulata Mathura isolate based on TAMS and 18S gene - KUMAR, SANJEEV; SHANKER, DAYA; PALIWAL, SANJHI; SUDAN, VIKRANT; GUPTA, KAPIL KUMAR; SRIVASTAVA, MUKESH (The Indian Journal of Animal Sciences, 2019)
The TAMS and 18S gene of local calf isolate from semiarid Mathura were amplified and used for phylogenetic analysis after custom sequencing. Results revealed phylogenetic association between Indian isolates in comparison to isolates across the world. Based on TAMS gene, the present isolates showed per cent homologies in the range 65.8–97.2% with various isolates across India and abroad. Likewise, 18S gene based per cent homologies of the present isolates varied from 70.5–100% with other isolates across India and abroad. The findings are important from molecular evolutionary point of view.